Models And Strategies for Developing the Electricity Sector in Indonesia as A Key Element for Poverty Eradication: Evaluation of The First Year - Sambodo, Maxensius Tri; Negara, Siwage Dharma; Ahmad Helmy Fuady; Inne Dwi Astuti (Journal of Indonesian Social Sciences and Humanities, 2016)
This study is part of multiyear research on electricity access at remote areas. The end goal of the study is to develop a model of electricity access in remote area. We collected a baseline information as part of quasi experimental study at some villages, in Satar Mese sub-district, East Nusa Tenggara. The baseline data showed three major finding. First, households with electricity access spent significantly less on kerosene. Second, access to electricity increases spending on non-food items significantly. Third, because the off grid SEHEN program is for lighting, we do not obtain strong evidence for a causal relation between electricity access and increases in working hours. We found that access to electricity can improve peoples welfare through increasing spending on food and non-food spending. This mechanism can work because the price of SEHEN is relatively cheaper than kerosene light. Thus, people obtained extra saving on energy spending. In the long terms, we expect, more jobs can be created when electricity production increases.